2023
DOI: 10.1371/journal.pone.0283742
|View full text |Cite
|
Sign up to set email alerts
|

A pragmatic evaluation of university student experience of remote digital learning during the COVID-19 pandemic, focusing on lessons learned for future practice

Abstract: The Covid-19 pandemic and subsequent national lockdowns resulted in drastic changes to the way that higher education was delivered. A mixed-methods research study was conducted to explore university students’ perceptions of online learning during the 2020/21 academic year. Students from across all Welsh higher education institutions were invited to participate. First, a series of focus groups (n = 13) were conducted to explore students’ experiences of online learning during the pandemic. Two were conducted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…HL requires thoughtful integration of experiences (Rasheed et al, 2020) in which teachers and students must manage multiple platforms, LMSs, and communication channels. Juggling between in-person and online assignments could increase workload and stress levels (Brown et al, 2023). A study by Mettis and Väljataga (2021) revealed that teachers had reservations about the potential of HL in providing "consistent learning experiences that emphasise higher order thinking levels, encompass contextual information and integrate knowledge from multiple disciplinary sources" (p. 498).…”
Section: Pedagogical Principles Underlying Hlmentioning
confidence: 99%
“…HL requires thoughtful integration of experiences (Rasheed et al, 2020) in which teachers and students must manage multiple platforms, LMSs, and communication channels. Juggling between in-person and online assignments could increase workload and stress levels (Brown et al, 2023). A study by Mettis and Väljataga (2021) revealed that teachers had reservations about the potential of HL in providing "consistent learning experiences that emphasise higher order thinking levels, encompass contextual information and integrate knowledge from multiple disciplinary sources" (p. 498).…”
Section: Pedagogical Principles Underlying Hlmentioning
confidence: 99%
“…Stine (2010) argued that demands of learning technology and academic rules and practices can result in mental stress and overload for students, which were even more serious during the Covid period (Sharin, 2021). In general, while some of these issues were ameliorated before the pandemic, the loss of community remained a problem in designing courses for online platforms (Brown et al 2023). Many of these issues were true for Japan where educational institutions at all levels were slow to adapt to online learning until Covid hit in 2018 (Wang & Cheng, 2021).…”
Section: Online Writing and Student-centered Learningmentioning
confidence: 99%
“…Chan and Ahn propose that improved performance on online unproctored exams is caused by factors other than cheating, specifically, reduced anxiety caused by sitting the exams at home, online, and unproctored. There is evidence that this was associated with reduced stress for some students, even during a global pandemic, but this is balanced by the stress of finding somewhere quiet to take the exam, with a reliable internet connection ( 5 ). Regardless, for this to lead to an increase of g = 0.7 on MCQs would be remarkable.…”
mentioning
confidence: 99%